Analisis Pengukuran Kinerja Karyawan KUD Menggunakan Metode Human Resources Scorecard (HRSC) dan Analitycal Hirarchy Process (AHP) - Fadilah, Amin Ikhfan; Kusumanto, Ismu; Suherman, Suherman; Nur, Muhammad; Hamdy, Muhammad Ihsan (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to measure employee performance and identify factors that influence employee performance. The methods used in this study are the human resource scorecard (HRSC) and the analytical hierarchy process (AHP) method. By integrating HR, strategy, goals, vision, and mission, 3 (three) strategic targets for the financial perspective were obtained; 3 (three) strategic targets for the customer perspective; 4 (four) strategic targets for the internal business process perspective; and 3 (three) strategic targets for the learning and growth perspective. The assessment system with the results was categorized into Traffic Light Systems. 13 strategic targets based on measurable scores from each perspective obtained 8 (eight) KPIs (Key Performance Indicators) categorized as green, 4 (four) KPIs categorized as yellow, and 1 (one) KPI categorized as red. Thus, it can be concluded that it is important to measure performance by involving human resources in an effort to achieve company goals.